Pendampingan Penggunaan Media Digital Sebagai Sarana Pemasaran Efektif Bagi Usaha Rumah Tangga Warga Sekitar Rptra Rasamala Kelurahan Menteng Dalam Kecamatan Tebet - Chendi Liana; Herta Armianti Soemardjo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2021)
In the digital era such as today’s, knowledge and understanding about the usage of social media as a marketing tool is very vital for those who are developing business. People tend to use digital media for many of their activities, including buying activities. More and more people search information about products they need using digital services, and then do many of their buying activities digitally. These facts forced new business - including home industries - to take up digital skills as well. That is why we see the importance of providing the community living around our partner – the Rasamala RPTRA – with accompaniment and assistance of the use of digital media for those who are doing small scaled business and home industries in this area. Observing that many residents living around the Rasamala RPTRA are traders and since the COVID-19 pandemic, the marketing of various products in general, and products from household businesses in particular, has become hampered. The use of digital media is currently a fairly effective marketing tool for small business actors to be able to adapt and survive with the current situation. The use of digital media such as social media will be able to reach consumers who have online shopping behavior caused by restrictions on activity movement. Therefore, one of the activities that can help residents around RPTRA Rasamala who have small businesses is to assist the use of digital media, such as social media to market products and communicate various product information online. The number of participants in this activity is 10 (ten) people who are owners of household businesses or small businesses. The implementation method of this activity has three stages, all of which are carried out online through zoom media, namely the first stagePknowledge internalization process in the form of education about various digital marketing media such as whatsapp marketing, e-commerce, instagram marketing, youtube marketing, and others, the second stage is the process of increasing understanding where at this stage participants are given back education about marketing communication and knowledge about digital media for product promotion and being able to identify online media that will be used in accordance with product marketing needs and adjust to consumer tastes, and the last is the third stage, namely the process of increasing skills in using digital marketing media, which is a process where all participants practice and apply it to their business products.As a result of this activity, all participants who have not utilized the use of online media as an effective marketing tool for their business products, now have additional knowledge and insight about marketing through digital media and now participants have used online media as a marketing medium so that their business products can survive in difficult situations. like this time. Keywords: Marketing, Digital Marketing Communication, Product, Small Business